Frequency of extrasystoles in healthy male employees. Issue 3 (March 1986) - Orth-Gomér, K; Hogstedt, C; Bodin, L; Söderholm, B
Abstract : To determine reference values for ectopic activity 147 actively employed healthy men aged from 15 to 65 years were examined by 24 hour Holter monitoring during their ordinary daily activities. Age was the only risk factor significantly associated with supraventricular and ventricular extrasystoles. During a six year follow up only two men died. In both the frequency of ventricular extrasystoles had been high, but neither of them died from cardiovascular disease. Because the distribution of the frequency of extrasystoles in the study group was highly skewed a percentile distribution was used to determine normal values. This distribution showed that 95% of men aged 15-39 years had less than 2.9 ventricular extrasystoles per hour and the same proportion of men aged 40 years or older had less than 36 ventricular extrasystoles per hour. For field studies values above the 90th percentile (that is more than 10 ventricular extrasystoles per hour for men 40 years or older) may be a more appropriate cut off point.